Selective targeting of microglia by quantum dots - Minami S Sakura; Sun Binggui; Popat Ketul; Kauppinen Tiina; Pleiss Mike; Zhou Yungui; Ward Michael E; Floreancig Paul; Mucke Lennart; Desai Tejal; Gan Li (Journal of Neuroinflammation, 2012)
Abstract Background Microglia, the resident immune cells of the brain, have been implicated in brain injury and various neurological disorders. However, their precise roles in different pathophysiological situations remain enigmatic and may range from detrimental to protective. Targeting the delivery of biologically active compounds to microglia could help elucidate these roles and facilitate the therapeutic modulation of microglial functions in neurological diseases. Methods Here we employ primary cell cultures and stereotaxic injections into mouse brain to investigate the cell type specific localization of semiconductor quantum dots (QDs) in vitro and in vivo. Two potential receptors for QDs are identified using pharmacological inhibitors and neutralizing antibodies. Results In mixed primary cortical cultures, QDs were selectively taken up by microglia; this uptake was decreased by inhibitors of clathrin-dependent endocytosis, implicating the endosomal pathway as the major route of entry for QDs into microglia. Furthermore, inhibiting mannose receptors and macrophage scavenger receptors blocked the uptake of QDs by microglia, indicating that QD uptake occurs through microglia-specific receptor endocytosis. When injected into the brain, QDs were taken up primarily by microglia and with high efficiency. In primary cortical cultures, QDs conjugated to the toxin saporin depleted microglia in mixed primary cortical cultures, protecting neurons in these cultures against amyloid beta-induced neurotoxicity. Conclusions These findings demonstrate that QDs can be used to specifically label and modulate microglia in primary cortical cultures and in brain and may allow for the selective delivery of therapeutic agents to these cells.